Cluster Nanozymes with Optimized Reactivity and Utilization of Active Sites for Effective Peroxidase (and Oxidase) Mimicking. Issue 5 (25th November 2021) - Zhang, Jieru; Wu, Tai‐Sing; Thang, Ho Viet; Tseng, Kai‐Yu; Hao, Xiaodong; Xu, Bingshe; Chen, Hsin‐Yi Tiffany; Peng, Yung‐Kang
Abstract: Single‐atom catalysts have attracted attention in the past decade since they maximize the utilization of active sites and facilitate the understanding of product distribution in some catalytic reactions. Recently, this idea has been extended to single‐atom nanozymes (SAzymes) for the mimicking of natural enzymes such as horseradish peroxidase (HRP) often used in bioanalytical applications. Herein, it is demonstrated that those SAzymes without constructing the reaction pocket of HRP still undergo the OH radical‐mediated pathway like most of the reported nanozymes. Their positively charged single‐atom centers resulting from support electronegative oxygen/nitrogen hinder the reductive conversion of H2 O2 to OH radicals and hence display low activity per site. In contrast, it is found that this step can be facilitated over their metallic counterparts on cluster nanozymes with much higher site activity and atom efficiency (cf. SAzymes with 100% atom utilization). Besides the mimicking of HRP in glucose detection, cluster nanozymes are also demonstrated as a better oxidase mimetic for glutathione detection. Abstract : Although single‐atom nanozymes have been reported to mimic peroxidases, they undergo the OH radical‐mediated pathway like most of nanozymes. In fact, OH radical generation (from H2 O2 ) over those cationic single‐atom centers is much slower than their metallic counterparts on conventional nanozymes. A cluster nanozyme with optimized site reactivity and utilization is demonstrated here to be a better candidate for peroxidase/oxidase mimicking.